Gut viral metagenomics identifies viral signatures and their role in depression - Chen, Xinyu; Wu, Jun; Fan, Dahua; Zhang, Peiwen; Li, Yan; Cao, Yongkai; Cao, Meiqun (Frontiers in Microbiology, 2025)
BackgroundThe gut microbiome has been implicated in the onset and progression of depression. Yet, the role of the gut virome in depression remains unexplored, and a diagnostic model has not been satisfactorily constructed.MethodsHerein, we analysed the gut virome profiles of 29 patients with depression and 33 healthy controls using bulk metagenome sequencing.ResultsA total of 45 differentially abundant viral taxa were identified, among which four, s_Stenotrophomonas_virus_Pokken, g_Pokkenvirus, s_Dickeya_virus_AD1, and g_Alexandravirus, demonstrated strong diagnostic potential (AUCs > 0.8). These four viruses also exhibited strong correlations, suggesting they may constitute a synergistic ecological cluster. Function annotation revealed seven metabolic pathways with significant differences, including alanine, aspartate, and glutamate metabolism, branched-chain amino acid (BCAA) biosynthesis, and energy metabolism in patients with depression.ConclusionThis study identified four distinct viral signatures for depression and proposes novel viral biomarkers for the diagnosis of depression, offering a robust diagnostic approach and new insights into the pathological mechanisms of depression.